2000
DOI: 10.1152/ajpgi.2000.278.4.g563
|View full text |Cite
|
Sign up to set email alerts
|

Diphenhydramine transport by pH-dependent tertiary amine transport system in Caco-2 cells

Abstract: Substrate specificity and pH dependence of the transport system for diphenhydramine were investigated in Caco-2 cell monolayers. Diphenhydramine uptake was not affected by any typical substrate for the renal organic cation transport system except procainamide. Along with procainamide, tertiary amine compounds with N-dimethyl or N-diethyl moieties in their structures inhibited the diphenhydramine uptake. Moreover, accumulation of diphenhydramine was stimulated by preloading the Caco-2 cells with these tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…Previously, we reported that transport of tertiary amines was mediated by the pH-dependent specific transport system in Caco-2 cells (Mizuuchi et al, 1999(Mizuuchi et al, , 2000a and also in the brush-border membrane vesicles (Katsura et al, 2000). Our previous findings also suggested that the transport system for tertiary amines would specifically recognize the N,Ndimethyl or N,N-diethyl moieties in tertiary amine compounds (Mizuuchi et al, 2000a).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Previously, we reported that transport of tertiary amines was mediated by the pH-dependent specific transport system in Caco-2 cells (Mizuuchi et al, 1999(Mizuuchi et al, , 2000a and also in the brush-border membrane vesicles (Katsura et al, 2000). Our previous findings also suggested that the transport system for tertiary amines would specifically recognize the N,Ndimethyl or N,N-diethyl moieties in tertiary amine compounds (Mizuuchi et al, 2000a).…”
Section: Discussionmentioning
confidence: 71%
“…Our previous findings also suggested that the transport system for tertiary amines would specifically recognize the N,Ndimethyl or N,N-diethyl moieties in tertiary amine compounds (Mizuuchi et al, 2000a). In contrast, nicotine consists of an N-methyl pyrrolidine ring and, therefore, a cyclic tertiary amine.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…An analogous nicotine/proton antiporter has also been characterized in kidney tubules, Caco-2, JAR, and LLC-PK1 cell lines (8,36,37). Many cationic organic drugs, such as clonidine, diphenhydramine, and MDMA, are similarly transported by a proton antiporter in Caco-2 cells (38)(39)(40). The trans-stimulation of the BBB transport of nicotine by diphenhydramine, naloxone, or tramadol suggests that they share the same transporter.…”
Section: Discussionmentioning
confidence: 97%
“…However, these earlier studies provided no information on the molecular and/or functional identity of this transporter, as evidence regarding this was obtained only recently (Koepsell et al, 2007). The carrier-mediated transport of DPH, which could involve the clonidine BBB transporter, was suggested to be present at the BBB and to work as an H + antiporter in Caco-2 cells (Au-Yeung et al, 2006;Goldberg et al, 1987;Mizuuchi et al, 2000). An H + antiporter for oxycodone was recently found in immortalized rat brain endothelial cells, as was a similar antiporter for MDMA in Caco-2 cells (Kuwayama et al, 2008;Okura et al, 2008).…”
Section: Discussionmentioning
confidence: 99%